Prestrain dependent viscoelastic model: Structural computation under dynamic loading. (1st August 2017) - Jalocha, D.; Constantinescu, A.; Neviere, R.
Abstract: The aim of this paper is to explore the effect of a prestrain dependent viscoelastic model on a complete structural computation under dynamic loading. The structure under consideration is a propellant based motor, used in launchers and boosters. The modeling takes into account the complete cycle life of the structure including a manufacturing and an in-service step. The computations are performed using standard finite elements and realized both with a linear and a prestrain dependent viscoelastic model in order to highlight the different prediction capabilities. The results exhibit a modification of the response of the structure under dynamic loading.